How heuristics in judgement influence the securities investment decision process - Marcel Piotrowski; Christian Bünnings (Journal of Financial Services Marketing, 2022)
Heuristics and biases are a widely researched topic in the field of behavioral finance. Yet, most studies only investigate the effects of heuristics and biases under laboratory conditions and consequently do not consider that financial decisions are likely to be made quite differently under laboratory conditions than in real life. Therefore, the purpose of our study is to investigate the effects of heuristics on the securities investment decision-making process in real-life financial advice conversations. To this end, we analyze the buying behavior of 200 individually observed retail customers of a German bank. Specifically, fifteen securities advisors were instructed to actively induce heuristics to measure how these cognitive biases distort customers' decision making with respect to purchase probability, one-time investment amount, and monthly savings plans. Our results indicate that heuristics in judgement affect the likelihood that customers purchase a product at all, but they do not seem to affect the amount of investment or the level of savings plans.
Keywords: 330; Affect heuristic; Anchor heuristic; Availability heuristic; Cognitive psychology; Decision-making; Securities investments; Financial advice